2017
DOI: 10.5098/hmt.9.23
|View full text |Cite
|
Sign up to set email alerts
|

Variable Heat Source and Wall Radiation Effects on Boundary Layer Convection From an Inclined Plate in Non-Darcian Porous Medium

Abstract: A semi -analytical investigation is performed to analyze the thermal convection flow with a radiation flux and a variable internal heat generation along an inclined plate embedded in a saturated porous medium. The flow in the porous medium is modeled with the Darcy-Brinkman law taking into account the convective term, while the temperature field is obtained from the energy equation. These governing equations with the boundary conditions are first cast into a dimensionless form by using a unique similarity tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The similarity method results found by Flilihi et al (2017Flilihi et al ( , 2019b are validated with those published in the literature and they showed a very good agreement.…”
Section: Comparison Of Cfd Calculation With Similarity Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The similarity method results found by Flilihi et al (2017Flilihi et al ( , 2019b are validated with those published in the literature and they showed a very good agreement.…”
Section: Comparison Of Cfd Calculation With Similarity Methodssupporting
confidence: 59%
“…The numerical results obtained by these authors are validated with experimental results. Afterward, Flilihi et al (2017) investigated the variable heat source and wall radiation effects on boundary layer convection from an inclined plate in non-Darcian porous medium. In this research, the problem is resolved numerically by a computational program based on the fifth order Runge-Kutta scheme coupled with shooting iteration technique.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results show that the temperature profile increases for the increasing of thermal conductivity parameter, Eckert number and heat generation parameter. Also, Flilihi et al (2017) investigated the variable heat source and wall radiation effects on boundary layer convection from an inclined plate in non-Darcian porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper is an extension of the works of Flilihi et al (2017Flilihi et al ( , 2019 to an unsteady convective boundary layer flow past an inclined plate in a non darcian porous medium in the presence of the viscous dissipation effects using the Darcy-Brinkman-Forchheimer model, which includes the effects of boundary and inertia forces taking into account the convective term. This study finds applications in the fields of petroleum engineering, geothermal energy, etc...…”
Section: Introductionmentioning
confidence: 99%